Human evolutionary genetics - Jobling, Mark A.; Jobling, Mark A. (Garland Science, 2013)
"Now in full color, this new edition of Human evolutionary genetics has been brought up-to-date with the many advances and discoveries made since the publication of the highly regarded first edition. The focus of the book is human genetic diversity: the mechanisms that generate it, how we study it, its implications in evolution, and its implications today. It will be an invaluable resource for anyone studying human evolution, genetic variation, population genetics, and biological anthropology"--